Study to assess internet usage patterns and prevalence of internet addiction among medical and engineering students of Bengaluru city - D. R., Sunil Kumar; Debata, Ipsita (International Journal Of Community Medicine And Public Health, 2018)
Background: Internet has become today, one of the most powerful tools for everybody, playing major roles in the life of adolescents. In tandem with the splurge in access to the Internet globally, with the rise of new-generation gadgets, the risk of “internet addiction” is emerging as a significant behavioral addiction pandemic to be tackled worldwide. Methods: A cross sectional study was carried out among 200 medical and engineering students, with 100 selected from each course. Data on internet usage patterns was collected by administering a semi-structured pre-tested questionnaire. Prevalence of internet addiction was estimated by using Young’s internet addiction scale. Results: The mean age of the participants was 18.85±0.197 years, among which 52% were females and 48% were males. While assessing internet usage patterns, it was found that the frequency of years of internet usage for 1-5 years was 80% (160) and that of internet use per day for 0-2 hours was 50.5% (101). Both these factors were significantly associated with internet addiction. Most common location of internet access was hostel, i.e. 51.5% (103). 93.5% (187) of students used Mobile phones and social media was found to be the main purpose for internet use which was 60% (120). Totally 67% (134) of medical and engineering students had internet addiction. Conclusions: The present study highlights the vulnerability of professional college students for internet addiction. Large scale epidemiological studies should be undertaken to assess the real problem and thereby take appropriate steps to tackle the growing problem.